Metal alloy catalyst for PEM electrolyzed water system and preparation method of metal alloy catalyst

The preparation of metal alloy catalysts composed of Ir and Ru elements by sol-gel method solves the problem of unstable phase structure of the existing Ir-based catalyst, and achieves high-efficiency and low-cost catalytic performance, which is suitable for PEM electrolytic system.

CN119776881AActive Publication Date: 2025-04-08CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411713063.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-08
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing Ir-based catalysts have unstable phase structure in an acidic environment, making it difficult to maintain long-term activity and stability, and iridium metal is expensive and has scarce reserves.

Method used

A metal alloy catalyst composed of Ir and Ru elements was prepared by sol-gel method. By adjusting the element molar ratio and preparation process, a face-centered cubic stacked iridium metal phase catalyst was formed, and the stability was improved through a two-stage program.

Benefits of technology

The uniform dispersion of Ir and Ru elements is achieved, the amount of precious metal Ir is used is reduced, the cost-effectiveness of the catalyst is improved, and the catalytic activity and stability are high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776881A_ABST
    Figure CN119776881A_ABST
Patent Text Reader

Abstract

The invention discloses a metal alloy catalyst for a PEM electrolyzed water system and a preparation method of the metal alloy catalyst, and the preparation method comprises the following steps: uniformly stirring a compound containing Ir and Ru elements, citric acid monohydrate, n-butyl alcohol, concentrated nitric acid and a polyoxypropylene-polyoxyethylene copolymer solution to form sol by adopting a sol-gel method, and heating and drying to form gel. The preparation method is simple and easy to implement, the dosage of precious metal Ir is low, the reaction process time is short, uniform dispersion of iridium and ruthenium elements can be achieved at normal pressure and low temperature, mass production is easy to achieve, and the finally prepared metal alloy catalyst has the advantages of being low in cost, high in catalytic activity, good in stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic materials, and in particular relates to a metal alloy catalyst for a PEM water electrolysis system and a preparation method thereof. Background Art

[0002] The scale of renewable energy power generation has expanded year by year, but the volatility and randomness of its power output have brought huge challenges to the consumption of green electricity. PEM water electrolysis to produce hydrogen has the advantages of strong start-stop / resilience, which can convert highly volatile renewable energy into high-quality hydrogen energy and achieve zero carbon emissions in the hydrogen production process. During the actual operation of the PEM electrolyzer, the four-electron transfer step on the anode oxygen evolution side is slow. Limited by the requirements of high overpotential and strong acidic environmental conditions, the catalysts that can be actually used in electrolyzers are still mainly Ir-based catalysts. However, iridium metal is expensive and scarce, and its activity still needs to be improved.

[0003] At present, many studies have been conducted to improve the activity and stability of Ir-based catalysts by introducing non-Ir element alloying methods, such as introducing Ca ions to prepare catalysts with IrO6 octahedral distortion (ACS Omega 2018, 3, 3, 2902–2908.), and preparing perovskite and pyrochlore-type catalysts (Nat Commun 9, 5236 (2018).; J.Am.Chem.Soc.2020, 142, 17, 7883–7888), all of which have achieved excellent OER activity. Peter Strasser et al. also obtained good stability by preparing IrNb oxide catalysts.

[0004] The above studies on Ir-based catalysts have effectively reduced the amount of precious metal Ir used. However, most of these alloyed Ir-based catalysts are difficult to maintain long-term stability due to their unstable phase structure. Therefore, selecting elements that are relatively stable in acidic environments and designing a stable bulk structure in an electrochemical environment is one of the effective ways to obtain catalysts that have both activity and stability. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a metal alloy catalyst for a PEM water electrolysis system.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] Dissolving citric acid monohydrate in deionized water at room temperature to obtain a first solution;

[0010] Adding chloroiridic acid and ruthenium nitrate to the first solution, and performing ultrasonic homogenization to obtain a second solution;

[0011] Adding n-butanol and concentrated nitric acid to the second solution, and performing ultrasonic homogenization to obtain a third solution;

[0012] Adding the polyoxypropylene-polyoxyethylene copolymer solution to the third solution, stirring and mixing to obtain a first sol;

[0013] drying the first sol to form a first gel;

[0014] The first gel is subjected to a two-stage program calcination, and after cooling to room temperature, first solid particles are obtained;

[0015] The first solid particles are washed with H2SO4, washed with deionized water, filtered and dried in sequence to obtain a metal alloy catalyst for a PEM water electrolysis system.

[0016] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, the molar ratio of the metal elements of chloroiridic acid and ruthenium nitrosylnitrate is 1-9:0-1.

[0017] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system described in the present invention, the molar ratio of the metal elements of the citric acid monohydrate to the chloroiridic acid and ruthenium nitrosyl nitrate is 4 to 0.5:1.

[0018] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, for every 1 mmol of the metal elements of chloroiridic acid and ruthenium nitrosyl nitrate, the amount of the polyoxypropylene-polyoxyethylene copolymer solution added is 0.5-2 mL.

[0019] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, the molar ratio of the metal elements of the n-butanol to the chloroiridic acid and the ruthenium nitrosyl nitrate is 30-15:1.

[0020] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, the molar ratio of the metal elements of the concentrated nitric acid to the chloroiridic acid and ruthenium nitrosyl nitrate is 70-80:1.

[0021] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, the drying temperature of the first sol is 110-130° C. and the drying time is 4-5 hours.

[0022] As a preferred embodiment of the method for preparing the metal alloy catalyst for the PEM water electrolysis system of the present invention, the temperature of the second stage of the programmed calcination is 300-550°C.

[0023] Another object of the present invention is to overcome the deficiencies in the prior art and provide a metal alloy catalyst for a PEM water electrolysis system.

[0024] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0025] The metal alloy catalyst is composed of Ir and Ru elements, and the specific composition is Ir x Ru y , 0.5≤x≤1, 0≤y≤0.5; the metal alloy catalyst is a face-centered cubic stacked iridium metal phase catalyst, ruthenium element is substitutionally doped at the iridium site, and the metal alloy catalyst particle size is 5 to 6 nm.

[0026] Beneficial effects of the present invention:

[0027] (1) The metal alloy catalyst for PEM water electrolysis system and its preparation method provided by the present invention can achieve uniform dispersion of iridium and ruthenium elements at normal pressure and relatively low temperature, with short reaction time, simple and easy preparation method, and easy to achieve mass preparation and large-scale production.

[0028] (2) When the metal phase iridium-ruthenium alloy catalyst prepared by the present invention is used as the anode catalyst material for PEM water electrolysis, the amount of precious metal Ir can be as low as 0.3 mg cm -2 , which has the advantages of low cost, high catalytic activity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0030] Figure 1 This is a flow chart of the preparation of the metal alloy catalyst in Example 1 of the present invention;

[0031] Figure 2 High-angle annular dark field scanning transmission (HAADF-STEM) image analysis and X-ray energy dispersive spectroscopy (EDS) image analysis of the catalyst prepared in Example 1 of the present invention;

[0032] Figure 3 This is a particle size analysis diagram of the catalyst prepared in Example 1 of the present invention;

[0033] Figure 4 The 2A cm2 in a PEMWE single electrolytic cell is shown in Example 1 of the present invention. -2 Constant current stability test diagram;

[0034] Figure 5 The catalysts prepared in Examples 1 and 2 of the present invention were subjected to electrochemical polarization curve tests in a three-electrode system;

[0035] Figure 6 Polarization curves of the catalysts prepared in Examples 1 and 2 of the present invention in a PEMWE single electrolytic cell;

[0036] Figure 7 XRD diagrams of the catalysts prepared in Examples 1 to 5 of the present invention;

[0037] Figure 8 The catalysts prepared in Comparative Examples 1 to 3 of the present invention were subjected to electrochemical polarization curve tests in a three-electrode system;

[0038] Fig. 9 The XRD pattern of the catalyst prepared in Example 6 of the present invention;

[0039] Fig.10 The catalysts prepared in Example 6 of the present invention and Comparative Example 6 were subjected to electrochemical polarization curve tests in a three-electrode system;

[0040] Fig.11 The catalyst prepared in Example 7 of the present invention was subjected to an electrochemical polarization curve test in a three-electrode system. DETAILED DESCRIPTION

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0044] The raw materials used in the present invention are commercially available unless otherwise specified.

[0045] Testing method involved in the present invention

[0046] Three-electrode test method: The reference electrode is mercury / mercurous sulfate, and the counter electrode is a carbon rod. The working electrode is prepared by coating the catalyst ink on a glassy carbon electrode with a diameter of 3 mm. The ink formula is 5 mg of catalyst and 50 μL of Nafion solution dispersed in 450 μL of ethanol, and ultrasonicated for at least 30 minutes to form a uniform ink. Then take 3.6 μL of the dispersion (containing 0.5 mg of catalyst) and drop it on the clean glassy carbon electrode, so that the catalyst loading on the electrode is 0.5 mg cm -2 The electrolyte used was 1MH2SO4. The test temperature was 30°C. First, at 50mV s -1 The working electrode was activated by cyclic voltammetry (CV) scanning in the potential range of 0.3-1.5 V (vs. RHE) at a scan rate of 5 mV s -1 Linear sweep voltammetry (LSV) tests were performed in the potential range of 1.1-1.7 V at a scan rate of 1.1 V.

[0047] Membrane electrode test method: Membrane electrode assembly (MEA) is performed using the catalyst coated membrane (CCM) method. 0.7 Ru 0.3 As the anode catalyst, commercial Pt / C was used as the cathode catalyst. The temperature of the electrolysis device was maintained at 80°C. After electrochemical activation, the polarization curve was tested. The stability of the membrane electrode was tested by 2A cm -2 The electrolysis voltage of the electrolytic cell under the current density is characterized.

[0048] Example 1

[0049] This embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system, specifically:

[0050] (1) Dissolve 0.4 mmol of citric acid monohydrate in 1 mL of deionized water at room temperature to obtain a first solution;

[0051] (2) adding chloroiridic acid containing 0.14 mmol of iridium element and ruthenium nitrosonitrate containing 0.06 mmol of ruthenium element to the first solution, and sonicating for 20 minutes to obtain a second solution;

[0052] (3) adding 4.2 mmol of n-butanol and 15.6 mmol of concentrated nitric acid to the second solution and ultrasonicating for 20 min to obtain a third solution;

[0053] (4) adding 1 mL of the polyoxypropylene-polyoxyethylene copolymer solution to the third solution and stirring for 2 h to obtain a first sol;

[0054] (5) drying the first sol at 120° C. for 4 h to form a first gel;

[0055] (6) placing the first gel in a tubular furnace, calcining at 250° C. for 2 h in the first stage and at 350° C. for 2 h in the second stage, and cooling to room temperature to obtain first solid particles;

[0056] (7) The first solid particles were washed with 100 mL of 0.5 M H2SO4 for 5 h, then washed with deionized water, filtered, and dried in a drying oven at 55°C for 12 h to obtain Ir 0.7 Ru 0.3 Metal phase catalysts.

[0057] The catalyst prepared in Example 1 was characterized by high-angle annular dark field scanning transmission (HAADF-STEM) imaging and X-ray energy spectrum (EDS) imaging. The results are as follows: Figure 2 shown.

[0058] The catalyst has clear and uniform lattice fringes, and the Ir and Ru elements are evenly dispersed. Figure 3 Particle size analysis shows that the alloy catalyst particle size is about 6nm.

[0059] The stability test of the catalyst prepared in Example 1 at 2A constant current was performed. Figure 4 As shown. Figure 4 It is obvious that after 550h of operation, Ir 0.7 Ru 0.3 The performance decay rate of the catalyst is only 7.74 μV / h, indicating that the catalyst has excellent oxygen evolution stability.

[0060] Example 2

[0061] The present embodiment provides a method for preparing a metal phase catalyst for a PEM water electrolysis system, wherein the content of iridium in the chloroiridic acid in step (2) of Example 1 is adjusted to 0.2 mmol, and no ruthenium nitrate is added, that is, the molar ratio of the metal elements of chloroiridic acid and ruthenium nitrate is 1:0, and the rest of the preparation process is the same as that of Example 1, to prepare an Ir metal phase catalyst.

[0062] The catalysts prepared in Examples 1 and 2 were subjected to electrochemical polarization curve tests in a three-electrode system. The results are as follows: Figure 5 As shown, the Ir prepared in Example 1 0.7 Ru 0.3 At 10mAcm -2 The overpotential at this current density is only 228.7 mV, which is much lower than the overpotential of Ir of 284.2 mV.

[0063] The catalysts prepared in Examples 1 and 2 were used as anode catalysts to assemble PEMWE single cells for performance testing. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the Ir prepared by the method of Example 1 0.7 Ru 0.3 The catalyst has a high oxygen evolution reaction activity in the PEM hydrolysis process, 2A·cm -2 The electrolysis voltage at this current density was only 1.75 V, compared to an overpotential of 1.78 V for the Ir catalyst.

[0064] The results of three-electrode and PEMWE single cell electrochemical tests both show that the catalyst performance of the formed IrRu alloy is better than that of single metal Ir.

[0065] Example 3

[0066] The present embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system. The iridium content in the chloroiridic acid in step (2) of the embodiment 1 is adjusted to 0.16 mmol, and the ruthenium content in the ruthenium nitrate is adjusted to 0.04 mmol, that is, the molar ratio of the metal elements in the chloroiridic acid and the ruthenium nitrate is 4:1. The rest of the preparation process is the same as that in the embodiment 1, and Ir is prepared. 0.8 Ru 0.2 Metal phase catalysts.

[0067] Example 4

[0068] The present embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system. The iridium content in the chloroiridic acid in step (2) of embodiment 1 is adjusted to 0.12 mmol, and the ruthenium content in the ruthenium nitrate is adjusted to 0.08 mmol, that is, the molar ratio of the metal elements in the chloroiridic acid and the ruthenium nitrate is 1.5:1. The rest of the preparation process is the same as that in embodiment 1, and Ir is prepared. 0.6 Ru 0.4 Metal phase catalysts.

[0069] Example 5

[0070] The present embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system, wherein the iridium content in the chloroiridic acid in step (2) of embodiment 1 is adjusted to 0.1 mmol, and the ruthenium content in the ruthenium nitrate is adjusted to 0.1 mmol, that is, the molar ratio of the metal elements in the chloroiridic acid and the ruthenium nitrate is 1:1, and Ir is prepared. 0.5 Ru 0.5 Metal phase catalysts.

[0071] The catalysts prepared in Examples 1 to 5 were subjected to XRD analysis, and the results were as follows: Figure 7 shown.

[0072] Depend on Figure 7 It can be seen that the characteristic peaks of the prepared Ir catalyst are consistent with the characteristic peaks of Ir single substance. 0.8 Ru 0.2 , Ir 0.7 Ru 0.3 , Ir 0.6 Ru 0.4 , Ir 0.5 Ru 0.5 The catalyst exhibits characteristic peaks similar to those of elemental Ir, which slightly shifts toward the Bragg large angle, indicating that the synthesized Ir 0.7 Ru 0.3 , Ir 0.6 Ru 0.4 , Ir 0.5 Ru 0.5 The catalyst is a similar metal phase, with Ru element substitutionally doped at the Ir site.

[0073] The catalysts prepared in Examples 2 to 5 were subjected to high-angle annular dark field scanning transmission (HAADF-STEM) image analysis, and the results showed that Figure 2 The catalysts prepared in Examples 3 to 5 were analyzed by X-ray energy spectrum (EDS) images, and the results were similar to those in Example 3. Figure 2 Similarly, it can be seen that the Ir and Ru elements are evenly dispersed.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 1 is that no citric acid monohydrate is added in step (1), and the rest of the preparation process is the same as that of Example 1 to prepare Ir 0.7 Ru 0.3 catalyst.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 1 is that no polyoxypropylene-polyoxyethylene copolymer solution is added in step (4), and the rest of the preparation process is the same as that of Example 1 to prepare Ir 0.7 Ru 0.3 catalyst.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1 is that n-butanol is not added in step (3), and the rest of the preparation process is the same as that of Example 1 to prepare Ir 0.7 Ru 0.3 catalyst.

[0080] The catalysts prepared in Comparative Examples 1 to 3 were subjected to electrochemical polarization curve tests in a three-electrode system. The results are as follows: Figure 8 As shown, the Ir prepared in Comparative Examples 1 to 3 0.7 Ru 0.3 At 10mAcm -2 The overpotentials under the current density are all higher than 228.7 mV in Example 1. This indicates that not adding citric acid, polyoxypropylene-polyoxyethylene copolymer solution, and n-butanol will have a negative impact on the electrochemical activity.

[0081] Example 6

[0082] This embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system. The temperature of the second stage in the calcination procedure in step (6) of embodiment 1 is adjusted to 300° C., 450° C., and 550° C., respectively. The rest of the preparation process is the same as that of embodiment 1. Ir 0.7 Ru 0.3 Alloy catalyst.

[0083] Comparative Example 4

[0084] The difference between this comparative example and Example 1 is that the temperature of the second stage in the calcination procedure in step (6) of Example 1 is adjusted to 750°C, 850°C, and 950°C respectively, and the rest of the preparation process is the same as that of Example 1 to prepare Ir 0.7 Ru 0.3 Alloy catalyst.

[0085] The Ir prepared in Example 6 and Comparative Example 4 0.7 Ru0.3 The catalyst was tested by XRD and electrochemical polarization curve in a three-electrode system. Figures 9-10 shown.

[0086] from Fig. 9 It can be seen that when the temperature of the second stage of calcination is 300°C, the prepared catalyst has characteristic peaks similar to those of Ir single substance, while at 450°C and 550°C, characteristic peaks similar to those of Ir single substance and rutile phase IrO2 appear at the same time, among which the catalyst obtained at 350°C has the best performance. The catalyst prepared in Comparative Example 4 only has characteristic peaks similar to those of rutile phase IrO2, and the catalytic performance shows a downward trend ( Fig.10 ).

[0087] Example 7

[0088] The present embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system. The amount of citric acid monohydrate in step (1) of embodiment 1 is adjusted to 0.1 mmol, 0.2 mmol, and 0.8 mmol, that is, the molar ratio of the metal elements of citric acid monohydrate to chloroiridic acid and ruthenium nitrate is adjusted to 0.5:1, 1:1, and 4:1. The remaining preparation process is the same as that of embodiment 1 to prepare Ir 0.7 Ru 0.3 Alloy catalyst.

[0089] The electrochemical polarization curve test of the catalyst prepared in Example 7 showed that it also had good electrochemical activity ( Fig.11 ), but slightly lower than that of Example 1, indicating that when the dosage of citric acid monohydrate is 0.4 mmol, that is, when the molar ratio of the metal elements of citric acid monohydrate to chloroiridic acid and ruthenium nitrosylnitrate is 2:1, the electrochemical activity of the catalyst is optimal.

[0090] Example 8

[0091] This embodiment provides a method for preparing a metal alloy catalyst for a PEM water electrolysis system. The addition amount of the polyoxypropylene polyoxyethylene copolymer solution in Example 1 is adjusted to 2 mL and 0.5 mL respectively, and the rest of the preparation process is the same as that in Example 1 to prepare Ir 0.7 Ru 0.3 Alloy catalyst.

[0092] The electrochemical polarization curve test was performed on the catalyst prepared in Example 8. The results showed that the catalyst prepared in Example 8 also had good electrochemical activity, but was slightly lower than that in Example 1, indicating that when the addition amount of the polyoxypropylene-polyoxyethylene copolymer solution was 1 mL, the electrochemical activity of the prepared catalyst was the best.

[0093] In summary, the present invention discloses a method for preparing a metal alloy catalyst for a PEM water electrolysis system. Compared with the prior art, there is no need to provide a reducing atmosphere. In the present invention, one end of the citric acid molecule is connected to a polyoxypropylene-polyoxyethylene copolymer solution, which is beneficial to the dispersion of metal elements. At the same time, during the calcination process, citric acid can also be used as a reducing agent to reduce high-valent metal ions.

[0094] The preparation method of the present invention adopts a sol-gel method, wherein a compound containing Ir and Ru elements, monohydrated citric acid, n-butanol, concentrated nitric acid and a polyoxypropylene-polyoxyethylene copolymer solution are stirred uniformly to form a sol, and then a gel is formed by heating and drying. The method is simple and easy to implement, and the amount of precious metal Ir used is low, the reaction process time is short, and the iridium and ruthenium elements can be uniformly dispersed at normal pressure and relatively low temperature, and mass production is easy to achieve. The prepared metal alloy catalyst has low cost, high catalytic activity and good stability.

[0095] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a metal alloy catalyst for a PEM water electrolysis system, characterized in that: include, Dissolving citric acid monohydrate in deionized water at room temperature to obtain a first solution; Adding chloroiridic acid and ruthenium nitrate to the first solution, and performing ultrasonic homogenization to obtain a second solution; Adding n-butanol and concentrated nitric acid to the second solution, and performing ultrasonic homogenization to obtain a third solution; Adding the polyoxypropylene-polyoxyethylene copolymer solution to the third solution, stirring and mixing to obtain a first sol; drying the first sol to form a first gel; The first gel is subjected to a two-stage program calcination, and after cooling to room temperature, first solid particles are obtained; the first solid particles are sequentially washed with H2SO4, washed with deionized water, filtered, and dried to obtain a metal alloy catalyst for a PEM water electrolysis system.

2. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The metal element molar ratio of the chloroiridic acid and the ruthenium nitrosyl nitrate is 1-9:0-1.

3. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The metal element molar ratio of the monohydrated citric acid to the chloroiridic acid and ruthenium nitrosyl nitrate is 4 to 0.5:

1.

4. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: For every 1 mmol of the metal elements of chloroiridic acid and ruthenium nitrosyl nitrate, the amount of the polyoxypropylene-polyoxyethylene copolymer solution added is 0.5-2 mL.

5. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The molar ratio of the metal elements of the n-butanol to the chloroiridic acid and ruthenium nitrosyl nitrate is 30-15:

1.

6. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The molar ratio of the metal elements of the concentrated nitric acid to the chloroiridic acid and ruthenium nitrosyl nitrate is 70-80:

1.

7. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The drying temperature of the first sol is 110-130° C., and the drying time is 4-5 hours.

8. The method for preparing a metal alloy catalyst for a PEM water electrolysis system according to claim 1, characterized in that: The temperature of the second stage of the programmed calcination is 300-550°C.

9. A metal alloy catalyst for a PEM water electrolysis system prepared by the preparation method according to any one of claims 1 to 8.

10. The metal alloy catalyst for a PEM water electrolysis system according to claim 9, characterized in that: The metal alloy catalyst is composed of Ir and Ru elements, and the specific composition is Ir x Ru y , 0.5≤x≤1, 0≤y≤0.5; the metal alloy catalyst is a face-centered cubic stacked iridium metal phase catalyst, ruthenium element is substitutionally doped at the iridium site, and the metal alloy catalyst particle size is 5 to 6 nm.

Citation Information

Patent Citations

  • Metal alloy catalyst and preparation method thereof

    CN111085195A

  • Ir / Ru alloy oxygen evolution catalyst and preparation method and application thereof

    CN111420658A

  • PtIr alloy nano material as well as preparation method and application thereof

    CN116037953A

  • Preparation method of amorphous IrOx / Ru catalyst for PEM water electrolysis hydrogen production

    CN116356361A